Compare the Effectiveness of Nulbuphine with Ropivacaine Versus Ropivacaine alone in Patients undergoing Upper Limb Surgeries - Faheem Asghar, Kamran Javaid, Umar Iqbal, Fahad Mansoor, Khumair Asif, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Ropinivacaine coupled with nulbuphine was used in this study to compare ropivacaine alone in the supraclavicular block. Study Design: Comparative/Randomized study Place and Duration: Anesthesia Deptt Sir Ganga Ram Hospital, Lahore. August 2020 to July 2021 Methods: There were 105 patients, with a range in age from 20 to 70 years, who underwent elective upper limb surgical procedures. A total of 108 patients were divided into two groups: group I consisted of 52 patients, while group II consisted of 53 patients. Group I received ropivacaine in combination with nulbuphine, while group II received ropivacaine in combination with normal saline (control). Comparisons and contrasts were made between the effectiveness of the two groups. The data was analyzed with the help of SPSS 22.0. Results: Using a p-value greater than 0.05, it was determined that there was no statistically significant difference between the two groups in terms of age, gender, body mass index, and American Society of Anesthesiologists (ASA) class I and II. A statistically significant difference (p=0.005) was found between the two groups in terms of sensory and motor block (see Table 1).The mean time of sensory blockage in group I was 427.13±15.62 minutes, whereas in group II it was 262.32±17.32 minutes. Mean time of motor block was also greater in group I than in group II (416.11±17.55 versus 231.19±16.71 ). There was a statistically significant difference in the duration of analgesia between groups I and II. Conclusion: Ropinivacaine 0.75 percent mixed with 10mg nulbuphine is particularly effective in supraclavicular brachial plexus block in terms of sensory and motor block, as well as analgesia duration when compared to ropivacaine alone.